Does Food Safety Build Customer Trust? The Mediating Role of Perceived Risk in Food Delivery Service in Bangkok during the COVID-19 Pandemic - Ratasuk, Akaraphun; Gajesanand, Sunanta (Asia Social Issues, 2022)
This research investigated the role of perceived food safety on customer trust and its mechanism via perceived risk in the food delivery service business during the COVID-19 pandemic. Survey data were collected from 600 food delivery customers in the Bangkok area. However, only 505 sets of questionnaires were completed and returned to the researcher with a response rate of 84.16%. The data were proceeded using WarpPLS 7.0 program to perform partial least squares Structural Equation Modeling (SEM), which was proven suitable for this research. The results showed that perceived food safety could directly promote customer trust (β=0.528; p<0.001). On the other hand, it can also indirectly foster customer trust by decreasing perceived risk (β=-0.123; p=0.003), which will eventually promote customer trust (β=-0.179; p<0.001). In other words, perceived risk partially mediates the association between perceived food safety and customer repurchase intentions (t=2.273; p=0.022). Therefore, customers' trust can be built by providing food safety standards to foster their confidence and perceive minimal risk levels. The findings provided additional empirical evidence of marketing knowledge that the social exchange theory can explain. The results can be applied as a guideline for food delivery service businesses to escalate their service and standards to build customer trust and gain competitive advantages, particularly during pandemics when customers are more health-conscious than ever.